Negotiating Whose Property It Is, for the Public Good. Issue 177 (March 2017) - Rhoades, Gary
Abstract : This chapter analyzes collective bargaining agreements in 4‐year institutions of higher education, examining language surrounding ownership, use, and distribution of the proceeds of intellectual property in distance education, and identifying ways in which the public good can be, and occasionally is, built in to contractual provisions.